2005
DOI: 10.1016/j.bbamem.2005.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized plasmid–lipid particles containing PEG-diacylglycerols exhibit extended circulation lifetimes and tumor selective gene expression

Abstract: Stabilized plasmid lipid particles (SPLP) consist of a single copy of DNA surrounded by a lipid bilayer. The particles are small ( approximately 100 nm), stable, monodisperse and have a low surface charge. A diffusible polyethylene glycol (PEG) coating attached to a lipid anchor is critical to the SPLP's functionality. The PEG-lipid exchanges out of the bilayer at a rate determined by the size of the lipid anchor. Here we show that SPLP can be prepared using a series of PEG-diacylglycerol lipids (PEG-S-DAGs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
158
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(164 citation statements)
references
References 29 publications
6
158
0
Order By: Relevance
“…It is known that PEG lipid with a long acyl chain, such as PEG-DSG, is retained strongly by a lipid membrane while PEG lipid with short acyl chain, such as PEG-DMG, dissociated more readily from a membrane [28]. After the incorporation of PEG-DSG, the stability of the optimized YSK05-MEND in serum was significantly increased, as expected ( Supplementary Fig.…”
Section: Pegylated Optimized Ysk05-mend Induces Gene Silencing Both Isupporting
confidence: 61%
See 1 more Smart Citation
“…It is known that PEG lipid with a long acyl chain, such as PEG-DSG, is retained strongly by a lipid membrane while PEG lipid with short acyl chain, such as PEG-DMG, dissociated more readily from a membrane [28]. After the incorporation of PEG-DSG, the stability of the optimized YSK05-MEND in serum was significantly increased, as expected ( Supplementary Fig.…”
Section: Pegylated Optimized Ysk05-mend Induces Gene Silencing Both Isupporting
confidence: 61%
“…[27] reported that the pharmacokinetics of the lipid nanoparticles (LNPs) with an ionizable aminolipid, which is largely neutral but changes to a cationic form under acidic conditions, was improved compared to that with a conventional cationic lipid. The LNPs system also succeeded in tumor specific reporter gene expression, and gene silencing in orthotopic and subcutaneous tumors [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…To improve the stability in the systemic circulation and the tumor accumulation, various groups have devised non-viral gene carriers with PEG. [13][14][15][16][17][18][19][30][31][32] Recently, cleavable PEG systems were developed, which are cleaved in response to an intracellular environment (e.g. low pH in endosome/ lysosomes, thiolytically small molecules, etc.…”
Section: Discussionmentioning
confidence: 99%
“…To resolve this dilemma, various devices have been developed. Ambegia et al 13 developed a strategy of exchangeable PEG-lipids. In the present study, we propose alternative strategy, involving a novel gene delivery system for cancer gene therapy, using a MEND modified with a tumor -specifically cleavable PEG-lipid.…”
Section: Introductionmentioning
confidence: 99%
“…Although preclinical studies in prostate cancer (16) and immune cells (17) are promising, distant tumor delivery has not been tested in the clinic. In order to mitigate this higher Peg-lipid content is used to improve the pharmacodynamic and biodistribution of LNP systems to the tumor site (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%